Effects of staggered transverse zigzag baffles and Al2O3–Cu hybrid nanofluid flow in a channel on thermofluid flow characteristics - Togun Hussein; Basem Ali; Abdulrazzaq Tuqa; Shashidhara Sumanth; Mohammed Hayder I.; Abed Azher M.; Al-Thamir Mohaimen; Sadeq Abdellatif M.; Biswas Nirmalendu; Yadav Krishna Kumar (Open Engineering)
This work examines the effects of staggered transverse zigzag baffles and hybrid nanofluid flow in a channel on the ferrofluid flow characteristics. The hybrid nanofluids Al2O3–Cu (2%) flow through the horizontal channel and are heated from the bottom. The W-shaped baffles, attached to the heated bottom wall, faced the right-hand side at an angle of 45° to the flow attack. Four different cases of baffle arrangements are also scrutinized. The mathematical models are analyzed numerically using the finite volume-based technique, adopting the k–w turbulence model. The key contribution of this study is the innovative combination of zigzag baffles with hybrid nanofluids, providing an effective passive method for improving heat transmission in industrial uses. The findings indicate substantial enhancements: a heat transfer improvement of up to 92.4% relative to smooth channel flow and a 48.5% increase in pressure drop. The research indicates that the orientation and positioning of the baffle substantially affect the density and intensity of created vortices, hence optimizing turbulence and flow redirection. Due to the reduction in the fluid velocity (initiated by the baffles) and increasing turbulence, the pressure in the flow passage increases with increasing Re, and the pressure reduces as the flow passes through the domain. The baffles’ direction has a considerable impact on the turbulence; the baffles’ top point and angle of direction also impact the flow direction and density of the swirls produced.